Humanism And Sustainability In The Islamic Education Curriculum: A Critical Analysis Of Arkoun's Ideas - Imam Mukhlis; Aqil Nizar Nasution; Brett Aaron Huggins (International Journal of Religion and Social Community, 2026)
The phenomenon of intensifying humanitarian crises and environmental degradation in the context of modern education demonstrates an urgent need to reconstruct the orientation of the Islamic Education curriculum to make it more adaptive and relevant. The theoretical landscape shows that Arkoun's sustainable humanism and critical epistemology approaches offer a potential conceptual framework to address these issues, but they have not yet been comprehensively integrated into curriculum design. This study aims to formulate an Islamic education curriculum model that combines humanistic values, ecological awareness, and critical thinking skills through a synthesis of sustainable humanism and critical epistemology. Using a descriptive qualitative method based on literature review, this study examines Arkoun's thinking and sustainable humanism theory to develop a systematic theoretical formulation. The results show that the integration of these two approaches can produce a more inclusive, reflective, and transformative curriculum paradigm, as well as strengthen the relevance of Islamic education in facing contemporary social, ecological, and epistemological challenges. In conclusion, this study offers an integrative model that can serve as the basis for curriculum reform in Islamic educational institutions, with recommendations for strengthening teacher competencies, revising the curriculum structure, and developing learning assessments that emphasise ethical, critical, and sustainability aspects.